Raman spectroscopy in forensic analysis: identification of cocaine and other illegal drugs of abuse. (January 2016) - de Oliveira Penido, Ciro Augusto Fernandes; Pacheco, Marcos Tadeu Tavares; Lednev, Igor K.; Silveira, Landulfo
Abstract : Current forensic methods for detecting and identifying cocaine and other drugs of abuse are destructive, so evidence cannot be re‐analyzed. Raman spectroscopy, based on inelastic light scattering, allows for rapid, inexpensive and nondestructive analysis in forensic science. This review presents the state‐of‐the‐art use of Raman spectroscopy as a confirmatory method for the identification of cocaine and other drugs of abuse in seized samples, including hidden compounds in legal materials such as beverages and clothes, among others, used for trafficking. Quantitative Raman spectroscopy is used to determine the actual drug concentrations in street cocaine and crack rocks and to identify possible adulterants in these samples for forensic toxicology and criminalistics. Finally, recent developments in Raman spectrometers (portable instruments and new excitation wavelengths) and advancements in data analysis offer exciting opportunities for new applications of Raman spectroscopy in the identification and quantification of drugs of abuse, including investigations conducted immediately at the scene of a crime. Copyright © 2016 JohnWiley & Sons, Ltd. Abstract : Current forensic methods for detecting and identifying cocaine and other drugs of abuse are destructive, so evidence cannot be re‐analyzed. Raman spectroscopy, based on inelastic light scattering, allows for rapid, inexpensive and nondestructive analysis in forensic science. This review presents the state‐of‐the‐art use of Raman spectroscopy as a confirmatory method for the identification of cocaine and other drugs of abuse in seized samples, including hidden compounds in legal materials such as beverages and clothes, among others, used for trafficking.